UNGKAPAN KASIH SAYANG DALAM KARYA LUKIS DEKORATIF - PRIH ARIFIN, Drs. Syafwan, M.Si, Dra.Zubaidah, M.Pd (Serupa The Journal of Art Education, 2015)
Human beings have unlimited imagination. Imaginations of the people try to make it come true, but sometimes make people complacent imagination and live in their fantasy world. When a person fall in love with something, someone could be not himself and was stuck in the fantasy of their own creation. On the way to achieve a sense of love is not only sweet and feels happy. Terkadangn sadness, disappointment, hurt, and tired of being colorful in the process of achieving a sense of love. It is what lies behind the writer to put it on the painting entitled "The phrase in The Art of Love".Departing from the problems of life and the problems experienced by humans, the end of this present work aims to provide an understanding that, as a human being should be able to live and deal with all the problems of life with realistic. and opened the eyes of the state of the current social environment. In the works of authors show characters or objects that represent the theme and in accordance with the concept of work. And each object has a relationship and mutual support to one another. Furthermore, the final work of this painting, decorative tends cultivation techniques to enhance dimensional shapes on object creation. With careful use of color to strengthen the expression and character of the object it self.An artist feel anxiety about what is seen, encountered and experienced from the surrounding environment. The effects of all the issues that have been passed in this life can assist in the achievement of the maturing process and maturity in attitude. Feelings that are then visualized into painting as something that would be contemplated returning to the learning process for writers and other human.